A Concise Appraisal of Cameroon’s Hazard Risk Profile: Multi-Hazard Inventories, Causes, Consequences and Implications for Disaster Management - Henry Ngenyam Bang (GeoHazards, 2022)
The paucity of a comprehensive document on Cameroon’s hazard/disaster risk profile is a limitation to the country wide risk assessment and adequate disaster resilience. This article narrows this gap by retrospectively exploring Cameroon’s hazard/disaster profile. This has been achieved through an investigative approach that applies a set of qualitative methods to derive and articulate an inventory and analysis of hazards/disasters in Cameroon. The findings indicate that Cameroon has a wide array and high incidence/frequency of hazards that have had devastating consequences. The hazards have been structured along four profiles: a classification of all hazard types plaguing Cameroon into natural, potentially socio-natural, technological, and social and anthropogenic hazards; occurrence/origin of the hazards; their impacts/effects to the ‘at risk’ communities/populace and potential disaster management or mitigation measures. In-depth analysis indicate that natural hazards have the lowest frequency but the potential to cause the highest fatalities in a single incident; potentially socio-natural hazards affect the largest number of people and the widest geographical areas, technological hazards have the highest frequency of occurrence; while social/anthropogenic hazards are the newest in the country but have caused the highest population displacement. Arguably, the multi-hazard/disaster inventory presented in this article serves as a vital preliminary step to a more comprehensive profile of Cameroon’s disaster risk profile.